Migration motivation of agriculturally educated rural youth: The case of Russian Siberia. (June 2016) - Bednaříková, Zuzana; Bavorová, Miroslava; Ponkina, Elena V.
Abstract: The migration of young people from rural areas is common in all agricultural regions of Russia, and Altai Krai, located in southwestern Siberia, is no exception. Out-migration, aversion to working in agriculture and the aging of farmers and farm managers are serious problems that raise questions about who will work in agriculture in the future. This paper aims to investigate factors that affect the decisions of agricultural students from Altai Krai to out-migrate or to return to their rural parental municipalities after finishing their university studies. We conducted a questionnaire survey of students at the Altai State Agrarian University in Barnaul and analyzed their migration intentions using a logit regression model. Migration motivation is studied in relation to personal and family background characteristics, employment expectations and quality of life, with a particular focus on references to agriculture. Our results show that the probability of leaving the parental municipality decreases if i) the respondent's parents support the study of agriculture, ii) the respondent's family owns agricultural land, iii) the respondent intends to work in agriculture, and iv) the respondent believes that it is not difficult to establish one's own business in the parental municipality. Women are more likely than men to leave their rural parental municipalities, and the probability of out-migration increases as respondents' life satisfaction increases. Our findings indicate that agricultural roots in the respondent's family stimulate young university graduates to return home and continue in the family tradition. Some of the factors that push young people, especially women, to out-migrate to cities (such as territorial isolation or the social roles of rural women) may be changed only over a long-term period. The recovery or enhancement of relationships between agricultural schools and agricultural enterprises, access to credits for business establishment and the purchase of agricultural land, and better living conditions in rural municipalities could encourage agriculturally educated youth to remain in rural areas and work in agriculture. Highlights: A strong link to agriculture decreases out-migration among agricultural students. The agricultural roots of a respondent's family motivate work in agriculture. Territorial isolation and social roles of rural women encourage out-migration. Business establishment and purchase of agricultural land require policy support.